Consensus-based recommendations for optimizing perioperative nutritional support and muscle health in major surgery in India - Chaudhary, Adarsh; Reddy, B. Ravinder; Rao, G. V.; Raveendran, Subhash; Mandal, Sanjoy; Radhakrishna, Patta; Dhar, Puneet; Krishnamurthy, Arvind; Doctor, Nilesh; Shaikh, Irfan; Deora, Ankita (Frontiers in Nutrition, 2025)
BackgroundMalnutrition and sarcopenia significantly affect outcomes in patients undergoing major surgery, leading to increased postoperative complications, prolonged recovery, and higher healthcare costs. Adequate perioperative nutritional support and muscle health optimization are crucial to improving these outcomes. This study aims to provide consensus-based recommendations for integrating perioperative nutritional practices along with the standard of care in patients undergoing major surgery.MethodsA modified Delphi process was employed with a panel of experts, and recommendations were made based on a comprehensive review of current evidence.ResultsThe expert panel reached a high level of agreement on the importance of early nutritional screening, including muscle health evaluation and use of oral nutritional supplements, multimodal prehabilitation (including exercise and nutritional optimization), and targeted postoperative interventions to enhance recovery, maintain muscle health, and reduce complications.ConclusionThe consensus recommendations provide a clear framework for integrating effective nutritional practices into routine surgical care. These strategies have the potential to significantly improve patient outcomes and reduce healthcare costs.